Pengaruh Biaya Operasional dan Beban Pajak terhadap Kemampuan Laba Bersih dengan Persediaan sebagai Variabel Moderasi Perusahaan Makanan dan Minuman yang terdaftar di BEI tahun 2014-2016 - Andi Purdiansyah; Nurasik Nurasik (Indonesian Journal of Law and Economics Review, 2018)
This study aims to in order to understand the the influence of the operational costs and the a heavy tax load against on wednesday its net profit, as well as the influence the operational costs and the a heavy tax load with supplies as pemoderasi on corporations foods and beverages in bei years 2014-2016. This research including the kind of research quantitative, with a population of the situation in the whole the food companies and strong drink he shall to that it is listed on a stock exchange a period of 2014-2016 with the total number of 16 companies. Sample the determination of the agent have been carried out with a method of purposive the sampling method of and obtained samples from 13 companies. An instrument of analysis that was used are analyzed to classical economic assumptions agreed to at, the regression coefficient of multiple linear, the test and been approved t and test it moderated regression analysis (MRA) by the use of the program spss version 20 for windows . The results of the study suggests that; 1) the cost of operational significant to net profit company, 2) the tax charges significant to net profit company, 3) supplies capable of strengthen the influence of between the cost of operational to net profit company, and 4) supplies strengthen the influence of between the tax charges against net profit company the food companies and strong drink he shall to that it is listed in the indonesia stock exchange years 2014-2016